Alumina as a thermoluminescent material - Uzun, Erdem; Yarar, Yasemin (AMER INST PHYSICS, 2007)
Thermoluminescence dosimeters are extensively used for quantitative dose measurements in various irradiation fields. They are also important for environmental monitoring after nuclear accident and weapon tests. In this work, the principles of TLD dosimeter and characteristics of several TLD materials are presented. Besides, taken into account the importance as a raw material, the utilization of domestic alumina (Al2O3) in TLDs as a thermoluminescent material is discussed.
Keywords: thermoluminescence; alumina; TLD; Physics